2014
DOI: 10.1186/s13049-014-0066-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of ischemic stroke in patients with mild traumatic brain injury: a nationwide cohort study

Abstract: BackgroundIt is known that the risk of stroke in patients with traumatic brain injury might be increased. However, the relationship between mild traumatic brain injury and ischemic stroke has never been established. We conducted a study of patients in Taiwan with mild traumatic brain injury to evaluate if they had a higher risk of stroke compared with the general population.MethodsWe utilized a sampled National Health Insurance claims database containing one million beneficiaries. We followed all adult benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 29 publications
2
51
0
Order By: Relevance
“…Other studies following these two have further exposed the association between stroke patients and previous TBI [25]. One study focused on the relationship between ischemic stroke and mild TBI and revealed mild TBI as a strong risk factor for ischemic stroke [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies following these two have further exposed the association between stroke patients and previous TBI [25]. One study focused on the relationship between ischemic stroke and mild TBI and revealed mild TBI as a strong risk factor for ischemic stroke [26]. …”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 The database contains comprehensive information on all insured individuals, including gender, date of birth, residential location, dates of clinical visits, the International Classification of Diseases (Ninth Revision) Clinical Modification (ICD-9-CM) diagnostic codes, details regarding prescribed medications, and outcomes at hospital discharge. 20 , 21 …”
Section: Methodsmentioning
confidence: 99%
“…The detailed ICD-9-CM codes for comorbidities are described elsewhere, and the processes used for selecting comorbidities are standard and widely accepted [19,21,22]. …”
Section: Methodsmentioning
confidence: 99%